ANALYZING THE WAREHOUSE MANAGEMENT SYSTEM AT PT. POS MANADO - Indriyani, Susi (Universitas Sam Ratulangi, 2020)
Abstract: Activities in warehouses are very important in implementing a warehouse management system. Warehouse management is concerned with ensuring that all activities involved in warehousing are carried out efficiently and effectively by those who work in warehouses. Warehouse is an activity to place goods from the process of receiving goods until they are issued for the process of shipping to consumers. This study aims to analyze the implementation of the warehouse management system. The purpose of this study is to analyze the process of implementing warehouse management system at PT. POS Manado.Â Keywords: Warehouse, Warehouse Management System, Implementation, Activities.